Senescence surveillance of pre-malignant hepatocytes limits liver cancer development - Kang, Tae-Won; Yevsa, Tetyana; Woller, Norman; Hoenicke, Lisa; Wuestefeld, Torsten; Dauch, Daniel; Hohmeyer, Anja; Gereke, Marcus; Rudalska, Ramona; Potapova, Anna; Iken, Marcus; Vucur, Mihael; et al. (Nature (London), 2011)
Senescence surveillance in cancer Oncogene-induced senescence has been shown to function as an intrinsic tumour suppressor mechanism. Lars Zender and colleagues now introduce the concept of 'senescence surveillance' by showing that premaligant senescent hepatocytes are cleared through a tumour antigen-directed immune response. This requires CD4 + T cells and suppresses the development of liver tumours in mouse models. The authors also provide evidence that senescent hepatocytes accumulate in the livers of immune-suppressed patients, demonstrating that senescence surveillance may also operate in humans. Strategies designed to harness antigen-specific immune surveillance of premalignant senescent cells may have potential in cancer prevention and therapy, and antigen-specific immune responses of this type may be relevant in vaccine production. Upon the aberrant activation of oncogenes, normal cells can enter the cellular senescence program, a state of stable cell-cycle arrest, which represents an important barrier against tumour development in vivo 1 . Senescent cells communicate with their environment by secreting various cytokines and growth factors, and it was reported that this ‘secretory phenotype’ can have pro- as well as anti-tumorigenic effects 2 , 3 , 4 , 5 . Here we show that oncogene-induced senescence occurs in otherwise normal murine hepatocytes in vivo . Pre-malignant senescent hepatocytes secrete chemo- and cytokines and are subject to immune-mediated clearance (designated as ‘senescence surveillance’), which depends on an intact CD4 + T-cell-mediated adaptive immune response. Impaired immune surveillance of pre-malignant senescent hepatocytes results in the development of murine hepatocellular carcinomas (HCCs), thus showing that senescence surveillance is important for tumour suppression in vivo . In accordance with these observations, ras-specific Th1 lymphocytes could be detected in mice, in which oncogene-induced senescence had been triggered by hepatic expression of Nras G12V . We also found that CD4 + T cells require monocytes/macrophages to execute the clearance of senescent hepatocytes. Our study indicates that senescence surveillance represents an important extrinsic component of the senescence anti-tumour barrier, and illustrates how the cellular senescence program is involved in tumour immune surveillance by mounting specific immune responses against antigens expressed in pre-malignant senescent cells.